The Housing Market Impacts of Shale Gas Development: Corrigendum - Muehlenbachs, Lucija; Spiller, Elisheba; Timmins, Christopher (American Economic Review, 2016)
The Housing Market Impacts of Shale Gas Development: Corrigendum by Lucija Muehlenbachs, Elisheba Spiller and Christopher Timmins. Published in volume 106, issue 2, pages 475 of American Economic Review, February 2016